Knowledge on Deep Vein Thrombosis and prevention practice among nurses in Hospital Universiti Sains Malaysia - Isa, Nur Shahirah (Pusat Pengajian Sains Perubatan, 2020)
Deep Vein Thrombosis (DVT) is a common thrombotic problem that usually affecting patient and it can lead to potentially life-threatening complication. The general objective of the study was to assess the level of knowledge on DVT and prevention practice among nurses in Hospital USM. A cross sectional study was conducted on 62 respondents recruited. A validated questionnaire was given to all respondent that fit with inclusion criteria. Then, the data was analyzed using Statistical Package for the Social Sciences (SPSS) software version 24.0. Descriptive statistic was used to describe the socio-demographic characteristic, level of knowledge on DVT and prevention practice among nurses in Hospital USM. Pearson’s Chi Square analyses were used to determine the association between socio-demographic data with level of knowledge on DVT and prevention practice among nurses in Hospital USM. 67.7% of participant had moderate level of knowledge on DVT, while 22.6% had low level and 9.7% had high level respectively. Then, majority of them had high level of practice which is 93.5%. This study also shown that there is no association between level of knowledge and level of prevention practice on DVT. It also revealed that there is no significant association between level of knowledge and prevention practice with sociodemographic data (years of working experience in hospital and previous attending workshop) on DVT among staff nurses in Hospital USM. Thus, increasing the knowledge and practice among nurses will prevent the complication of DVT to occur.